1998
DOI: 10.1002/(sici)1097-4660(1998110)73:3<175::aid-jctb936>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Feed supplement recovered from dairy wastewater by biological and chemical pretreatment

Abstract: : A continuous process for treatment of dairy wastewater with immobilized lactic acid bacteria has been demonstrated at pilot scale. A strain of L actobacillus plantarum was selected on the basis of a high conversion rate of lactose at low pH, a high affinity of lactose at low concentrations, and the ability to retain activity for a long time immobilized in alginate beads. Lactose was converted to lactic acid, which lowered the pH and precipitated milk proteins. The proteins were separated together with milk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…However, other possible applications may now be available due to this expanded operation range of pH. It has previously been reported that immobilized lactic acid bacteria can maintain high activities after short exposures to extreme pH values (Dyrset et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other possible applications may now be available due to this expanded operation range of pH. It has previously been reported that immobilized lactic acid bacteria can maintain high activities after short exposures to extreme pH values (Dyrset et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, other possible applications may now be available due to this expanded operation range of pH. It has previously been reported that immobilized lactic acid bacteria can maintain high activities after short exposures to extreme pH values (Dyrset et al 1998). An interesting observation from Figs 3, 5 and 7 is that high rates of cell release and lactate production were maintained at pH values that normally would cause severely depressed growth rates in free cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria ferment soluble lactose to lactic acid, which denatures milk proteins in the wastewater. In combination with CMC, the total COD was reduced by 65-78 %, while reduction of 49-82 % was obtained when chitosan was used (60). At an initial 5 g/L of COD, over 0.01 g/L of proteins and 0.7-0.8 g/L of sugars, 75, >90 and 10-25 % of COD were removed, respectively (61).…”
Section: Physicochemical Treatmentmentioning
confidence: 99%
“…As informações são escassas -ou mesmo inexistentes -nos meios de divulgação técnico-científica que tratam do assunto sobre o reuso dos sólidos do leite presentes no retido. Em razão dessa falta de informação, a sugestão é destinar estes nutrientes para ração animal (DYRSET et al, 1998), enquanto que estes sólidos lácteos de alto valor biológico poderiam ser reutilizados no processo como insumo de outros derivados, como doce de leite, bebida láctea ou composto lácteo.…”
Section: Introductionunclassified